Method for regulating and controlling viscosity of mineral wool melt from spodumene lithium extraction tailings
By mixing the lithium-extracted tailslag with basalt and dolomite and using the new acidity coefficient formula to calculate, the melt viscosity of mineral wool is regulated, and the problem of difficult use of spodumene lithium-extracted tailslag is solved, achieving efficient resource recycling and production cost reduction.
Patent Information
- Application Number
- CN202411750942.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-25
AI Technical Summary
The existing technology is difficult to effectively utilize spodumene to extract lithium tailings, resulting in its storage and environmental pollution problems. At the same time, the traditional acidity coefficient calculation formula cannot accurately predict the high-temperature melt viscosity of mixed materials.
By mixing the lithium-extracted tailings with basalt and dolomite, and using the new acidity coefficient formula (the ratio of the sum of SiO2+Al2O3+TiO2 content and the sum of Fe2O3+CaO+MgO+Na2O+K2O content), the melt viscosity of mineral wool is regulated to ensure the effective use of lithium-extracted tailings in mineral wool production.
The high-value utilization of lithium-extracted tailslag has been achieved, which reduces production costs, ensures the stability of melt viscosity in mineral wool production, reduces equipment losses, and promotes the industrialization process of resource utilization of lithium-extracted tailslag.
Smart Images

Figure CN119683849A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for regulating the viscosity of a mineral wool melt by using tailings of lithium extraction from spodumene, and belongs to the technical field of resource utilization of mining and metallurgical solid waste. Background Art
[0002] Mineral wool is a thermal insulation material made from natural rock that has been fused at high temperatures and then fiberized. Its main features are excellent high temperature resistance, good sound insulation, corrosion resistance and fire resistance. It is widely used in thermal insulation and acoustic control in the fields of construction, industry, and shipbuilding. Mineral wool can not only effectively improve energy efficiency and reduce energy consumption, but also help improve the comfort and safety of buildings. In addition, the production process of mineral wool is also relatively environmentally friendly and meets the standards of green building materials.
[0003] Raw materials are one of the main factors that determine the production and quality of mineral wool. Existing mineral wool production usually uses basalt, dolomite and slag as raw materials. Through reasonable ore blending, the mixed materials reach a certain melt viscosity range after high-temperature melting, which is convenient for fiberization and cotton formation, and then obtain mineral wool products of different specifications through subsequent processing. The chemical composition of the mixed materials composed of different raw material ratios is an important factor in determining the acidity coefficient and high-temperature melt viscosity of the material. Reasonable ore blending according to the source and origin of natural ore and slag is a prerequisite for ensuring the production of mineral wool. The most important factor is the content of the main chemical components such as SiO2, Al2O3, CaO and MgO in the raw materials.
[0004] Spodumene (LiAlSi2O6) is a common lithium ore and the main lithium-containing ore raw material for industrial lithium extraction and production of lithium carbonate in my country. The residual tailings from lithium extraction from spodumene (hereinafter referred to as lithium tailings) are the solid waste remaining after spodumene undergoes the sulfuric acid method to chemically extract lithium. Industrial production practice shows that when using spodumene as a raw material and using sulfuric acid method to extract lithium, about 10 tons of lithium tailings will be produced for every ton of lithium carbonate product produced. Therefore, the amount of lithium tailings produced is large, and generally not fully recycled and can only be stored and disposed of, making it an important burden for lithium salt production enterprises. Especially in the past decade, with the rapid development of my country's new energy industry, the demand for lithium carbonate has shown a nearly exponential growth, and the amount of lithium tailings produced has also shown a nearly exponential growth. In the absence of effective bulk consumption, the safe disposal of lithium tailings requires a large amount of space, which seriously restricts the green and sustainable development of the lithium salt industry. In addition, since lithium tailings contain a variety of mineral elements, if they can be used as resources through reasonable technical means, they can bring added value to the industry and reduce environmental pressure.
[0005] In recent years, with the improvement of environmental protection requirements and the popularization of the concept of resource recycling, in order to solve the practical dilemma of the difficulty in disposing of the residual tailings from spodumene lithium extraction, relevant technologies and patents have been reported on the disposal and high-value utilization of lithium extraction tailings (production of building materials, preparation of adsorption materials, multi-component recovery of minerals, etc.). For example, in the field of multi-component graded and quality-based recovery of lithium extraction tailings, Chinese patent CN117165787A discloses a method for extracting lithium from spodumene and simultaneously recovering low-iron and low-sulfur silicon-aluminum powder, high-purity gypsum, tantalum-niobium concentrate and lithium-rich iron material; Chinese patent CN118847346A discloses a method for preparing gypsum, volcanic ash mixture and silicon-aluminum powder from spodumene smelting slag; Chinese patent CN116532235A discloses a method for comprehensive resource utilization of spodumene smelting slag; Chinese patent CN108273826A discloses a method for full-phase high-value recovery of lithium slag; Chinese patent CN115448318A discloses a method for comprehensive recovery of silicon and aluminum extracted from lithium slag, etc. For example, in the aspect of the use of lithium tailings for building materials, Chinese patent CN117756487A discloses a lithium slag cementitious material and its preparation method, Chinese patent CN117361917A discloses a lithium slag composite admixture and its preparation method and a shotcrete, Chinese patent CN114249549A discloses a method for producing early strength cement using lithium slag, etc. For another example, in the aspect of the application of lithium tailings for high-value adsorption materials, Chinese patent CN118925661A discloses a lithium slag-based ion sieve adsorbent and its preparation method, lithium ion adsorption column, Chinese patent CN115323195A discloses a method for extracting lithium from brine by adsorption using lithium smelting slag, Chinese patent CN 111018422A discloses a porous self-supporting zeolite material prepared by acid-process lithium slag, its preparation method and application, etc. Although the above patented technology provides many references for the multi-channel reuse of lithium tailings, it also faces many challenges. For example, the saturation of the traditional construction industry has made the application of lithium tailings in cement, concrete and other fields face many challenges; at the same time, lithium tailings as adsorption materials are difficult to achieve the realistic goal of large-scale consumption of lithium tailings raw materials, and the fluctuation of the chemical composition of lithium tailings limits the application of products; in terms of the classification and quality recovery of multi-mineral phase components of lithium tailings, the overall processing cost and the stability of multi-component products and their terminal applications have not been completely solved.
[0006] It can be seen that how to achieve large-scale disposal of lithium tailings has not yet been solved. It is crucial to find new lithium tailings disposal routes and provide relatively mature technical solutions for the large-scale utilization of lithium tailings. Since lithium tailings are the residual products after lithium extraction from spodumene, their main chemical composition is silicon dioxide and aluminum oxide. Therefore, lithium tailings have the potential to be used in mineral wool production. However, since the doping of lithium tailings will cause changes in the high-temperature melt viscosity of the mixed material, the current traditional mineral wool production acidity coefficient calculation formula (the ratio of the sum of SiO2+Al2O3 content to the sum of CaO+MgO content) cannot effectively reflect and predict the high-temperature melt viscosity of the mixed material. Therefore, it is urgent to develop a new method to regulate the melt viscosity of mineral wool containing spodumene lithium tailings to ensure the effective utilization of lithium tailings in mineral wool production. Summary of the invention
[0007] The first object of the present invention is to provide a method for regulating the viscosity of mineral wool melt by using spodumene lithium extraction tailings.
[0008] To achieve the first object of the present invention, the method comprises:
[0009] The lithium extraction tailings are mixed with basalt and dolomite to obtain a mixed material, and the mixed material is subjected to a heat treatment to obtain a high-temperature melt; the acidity coefficient of the mixed material is calculated using formula (I):
[0010] Acidity coefficient = [M(SiO2)+M(Al2O3)+M(TiO2)] / [M(Fe2O3)+M(CaO)+M(MgO)+M(Na2O)+M(K2O)] formula (I);
[0011] Among them, M(SiO2), M(Al2O3), M(TiO2), M(Fe2O3), M(CaO), M(MgO), M(Na2O), and M(K2O) represent the mass percentage of silicon dioxide, aluminum oxide, titanium dioxide, iron oxide, calcium oxide, magnesium oxide, sodium oxide, and potassium oxide, respectively, in the form of oxides.
[0012] In a specific embodiment, the lithium extraction tailings are pre-treated by drying to make its water content lower than 3wt%.
[0013] In a specific embodiment, the particle size of the lithium extraction tailings, basalt, and dolomite is less than 0.074 mm.
[0014] In a specific embodiment, the content of lithium extraction tailings in the mixed material is 10wt% to 30wt%, the content of dolomite is 17.5wt% to 40wt%, and the rest is basalt.
[0015] In a specific embodiment, the SiO2 content of the lithium extraction tailings is 54.06wt%~70.6wt%, the Al2O3 content is 22.03wt%~25.39wt%, the TiO2 content is 0.03wt%~0.08wt%, the CaO content is 0.99wt%~7.7wt%, the MgO content is 0.04wt%~0.09wt%, the Fe2O3 content is 0.9wt%~1.34wt%, the Na2O content is 0.05wt%~0.36wt%, and the K2O content is 0.55wt%~0.85wt%.
[0016] In a specific embodiment, the dolomite has a SiO2 content of 9.24wt% to 16.26wt%, an Al2O3 content of 1.83wt% to 2.64wt%, a TiO2 content of 0.2wt% to 1.84wt%, a CaO content of 32.68wt% to 53.97wt%, a MgO content of 18.52wt% to 24.37wt%, a Fe2O3 content of 1.85wt% to 2.02wt%, a Na2O content of 0.06wt% to 1.32wt%, and a K2O content of 0.38wt% to 1.06wt%.
[0017] In a specific embodiment, the basalt has a SiO2 content of 43.99wt% to 52.84wt%, an Al2O3 content of 13.52wt% to 14.03wt%, a TiO2 content of 2.81wt% to 3.32wt%, a CaO content of 7.35wt% to 10.4wt%, a MgO content of 4.94wt% to 8.73wt%, a Fe2O3 content of 8.26wt% to 16.01wt%, a Na2O content of 1.67wt% to 2.23wt%, and a K2O content of 2.15wt% to 3.27wt%.
[0018] In a specific embodiment, the acidity coefficient is 1.37 to 1.77.
[0019] The second object of the present invention is to provide a kind of mineral wool regulated by tailings of lithium extraction from spodumene.
[0020] In order to achieve the second object of the present invention, the mineral wool is prepared by the method of regulating the melt viscosity of the mineral wool using the tailings of lithium extraction from spodumene.
[0021] In a specific embodiment, the high temperature melt viscosity of the mineral wool is 0.57-6.48 Pa·s in the temperature range of 1350-1550°C.
[0022] Beneficial effects:
[0023] 1. The present invention introduces industrial spodumene lithium extraction tailings into the mineral wool production system as part of the melt raw material, realizes the high-value utilization of lithium extraction tailings, reduces the storage and environmental pollution problems of lithium extraction tailings, can effectively reduce the discharge of industrial waste residues, and realizes the recycling of resources;
[0024] 2. The present invention replaces part of the natural mineral raw materials such as basalt and dolomite with silicon, aluminum and other components in the lithium extraction tailings, thereby reducing the raw material procurement cost, further reducing the production cost, and facilitating promotion and use;
[0025] 3. The acidity coefficient formula of the present invention (the ratio of the sum of SiO2+Al2O3+TiO2 contents to the sum of Fe2O3+CaO+MgO+Na2O+K2O contents) can better reflect the relationship between the acidity coefficient and the high-temperature melt viscosity of the mineral wool production mixture, and can make a quick and accurate judgment on the high-temperature melt viscosity of the mixture.
[0026] 4. The present invention can accurately control the melt viscosity by rationally proportioning the lithium tailings with other raw materials, thereby ensuring the homogeneity of the melt, ensuring its fluidity and stability in the high-temperature fiberization process, and further reducing equipment loss;
[0027] 5. The process design of the present invention is simple and has a wide range of applications. By adjusting the proportion of ingredients, it can meet the production needs of various mineral wool. With the rapid development of the spodumene lithium extraction industry, the output of lithium tailings has increased year by year. The present invention provides an effective solution for recycling lithium tailings, and promotes the industrialization process of resource utilization of lithium tailings.
[0028] 6. The lithium tailings of the present invention account for 10wt% to 30wt% of the raw materials for mineral wool production. The acidity coefficient of the mixed material (composed of basalt, dolomite and lithium tailings) used for mineral wool production is between 1.37 and 1.77, and the high-temperature melt viscosity is 0.57 to 6.48 Pa·s in the temperature range of 1350 to 1550°C, which meets the use standard for mineral wool production; at the same time, the lithium tailings doping can improve the high-temperature melt fluidity of the mixed material for mineral wool production, which is beneficial to the melting of the mixed material, and the appropriate melt viscosity for mineral wool production can be obtained at a relatively low temperature, thereby facilitating energy saving and consumption reduction in the mineral wool production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A process flow chart of a method for regulating the viscosity of mineral wool melt based on spodumene lithium extraction tailings provided in an embodiment of the present invention;
[0030] Figure 2The relationship between the acidity coefficient of the mineral wool production mixture and the high-temperature melt viscosity under different temperature conditions is based on the acidity coefficient formula of the present invention, that is, the ratio of the sum of the SiO2+Al2O3+TiO2 content to the sum of the Fe2O3+CaO+MgO+Na2O+K2O content;
[0031] Figure 3 The relationship between the acidity coefficient of mineral wool production mixture and high-temperature melt viscosity under different temperature conditions is based on the traditional acidity coefficient calculation formula, that is, the ratio of the sum of SiO2+Al2O3 content to the sum of CaO+MgO content. DETAILED DESCRIPTION
[0032] To achieve the first object of the present invention, the method comprises:
[0033] The lithium extraction tailings are mixed with basalt and dolomite to obtain a mixed material, and the mixed material is subjected to a heat treatment to obtain a high-temperature melt; the acidity coefficient of the mixed material is calculated using formula (I):
[0034] Acidity coefficient = [M(SiO2)+M(Al2O3)+M(TiO2)] / [M(Fe2O3)+M(CaO)+M(MgO)+M(Na2O)+M(K2O)] formula (I);
[0035] Among them, M(SiO2), M(Al2O3), M(TiO2), M(Fe2O3), M(CaO), M(MgO), M(Na2O), and M(K2O) represent the mass percentage of silicon dioxide, aluminum oxide, titanium dioxide, iron oxide, calcium oxide, magnesium oxide, sodium oxide, and potassium oxide, respectively, in the form of oxides.
[0036] The mixing may be mechanically mixing lithium tailings, basalt powder and dolomite powder, and the mechanical mixing equipment used may be one of a horizontal ribbon mixer, a high-speed mixer, a high-efficiency circulating mixer, a mechanical fusion machine and a drum mixer. By weighing the lithium tailings, basalt and dolomite in a certain proportion and then mechanically mixing them to obtain a mixed material, it is possible to ensure that the lithium tailings, basalt powder and dolomite powder are evenly distributed, avoid melt viscosity fluctuations caused by uneven distribution of components during subsequent melting, and make the subsequent high-temperature melting process more stable, which is conducive to obtaining a high-temperature melt with uniform properties.
[0037] The mixed material is heated mainly by an electric heating furnace.
[0038] In a specific embodiment, the lithium extraction tailings are pre-treated by drying to make its water content lower than 3wt%.
[0039] Among them, the water content of lithium extraction tailings is reduced by drying pretreatment. This is mainly because the lithium extraction tailings are the residual tailings of lithium extraction by spodumene sulfuric acid leaching. Therefore, industrial lithium extraction tailings usually contain higher water content, which is not conducive to the subsequent reuse of lithium extraction tailings: high-water content lithium extraction tailings are prone to agglomeration during use, which brings difficulties to subsequent processing links such as transportation and mixing; at the same time, high water content will lead to an increase in the total mass of the material, which is not conducive to the homogenization of mineral wool production raw materials (a mixture of basalt, dolomite and lithium extraction tailings), and will cause melt viscosity fluctuations and equipment loss during high-temperature melting; in addition, too high water content in lithium extraction tailings will make it difficult to operate the lithium extraction tailings during the blending process with basalt and dolomite, making the chemical composition of the mixed material difficult to predict.
[0040] In a specific embodiment, the particle size of the lithium extraction tailings, basalt, and dolomite is less than 0.074 mm.
[0041] Experiments show that controlling the particle size below 0.074 mm can prevent agglomeration.
[0042] In a specific embodiment, the content of lithium extraction tailings in the mixed material is 10wt% to 30wt%, the content of dolomite is 17.5wt% to 40wt%, and the rest is basalt.
[0043] In a specific embodiment, the SiO2 content of the lithium extraction tailings is 54.06wt%~70.6wt%, the Al2O3 content is 22.03wt%~25.39wt%, the TiO2 content is 0.03wt%~0.08wt%, the CaO content is 0.99wt%~7.7wt%, the MgO content is 0.04wt%~0.09wt%, the Fe2O3 content is 0.9wt%~1.34wt%, the Na2O content is 0.05wt%~0.36wt%, and the K2O content is 0.55wt%~0.85wt%.
[0044] In a specific embodiment, the dolomite has a SiO2 content of 9.24wt% to 16.26wt%, an Al2O3 content of 1.83wt% to 2.64wt%, a TiO2 content of 0.2wt% to 1.84wt%, a CaO content of 32.68wt% to 53.97wt%, a MgO content of 18.52wt% to 24.37wt%, a Fe2O3 content of 1.85wt% to 2.02wt%, a Na2O content of 0.06wt% to 1.32wt%, and a K2O content of 0.38wt% to 1.06wt%.
[0045] In a specific embodiment, the basalt has a SiO2 content of 43.99wt% to 52.84wt%, an Al2O3 content of 13.52wt% to 14.03wt%, a TiO2 content of 2.81wt% to 3.32wt%, a CaO content of 7.35wt% to 10.4wt%, a MgO content of 4.94wt% to 8.73wt%, a Fe2O3 content of 8.26wt% to 16.01wt%, a Na2O content of 1.67wt% to 2.23wt%, and a K2O content of 2.15wt% to 3.27wt%.
[0046] In a specific embodiment, the acidity coefficient is 1.37 to 1.77.
[0047] In order to achieve the second object of the present invention, the mineral wool is prepared by the method of regulating the melt viscosity of the mineral wool using the tailings of lithium extraction from spodumene.
[0048] In a specific embodiment, the high temperature melt viscosity of the mineral wool is 0.57-6.48 Pa·s in the temperature range of 1350-1550°C.
[0049] The specific implementation of the present invention is further described below in conjunction with the examples, but the present invention is not limited to the scope of the examples. The experiments in the examples are consistent with the requirements for particle size, and the particle sizes of lithium slag, basalt and dolomite are all controlled to be below 0.074 mm.
[0050] Example 1
[0051] According to the technical solution and Figure 1 The process shown in the embodiment is to carry out relevant experiments using the residual tailings of lithium extraction from spodumene in Suining, Sichuan. The chemical composition thereof and the chemical composition of basalt and dolomite in Hebei are shown in Table 1. The acidity coefficient is calculated according to the chemical composition parameters (the acidity coefficient is defined as the ratio of the sum of the contents of SiO2+Al2O3+TiO2 to the sum of the contents of Fe2O3+CaO+MgO+Na2O+K2O).
[0052] Table 1 Chemical composition analysis results of mineral wool production raw materials (percentage content)
[0053]
[0054] Note: The method for analyzing the chemical composition of each material in the embodiment is to take a small amount of sample and dry it at 105°C for more than two hours to ensure that the moisture of the sample is volatilized before performing X-ray fluorescence spectrum analysis; the preparation process of the mixed material is to take the corresponding mass of each raw material (containing a certain amount of moisture) for mechanical mixing. The chemical composition of the mixed material described in the table is the actual measurement value of the X-ray fluorescence spectrometer.
[0055] Experimental process: 20g of lithium extraction tailings with a moisture content of less than 3% after drying pretreatment was taken, and 40g of basalt and 40g of dolomite were mechanically mixed to obtain a mixed material 1 (that is, the lithium extraction tailings accounted for 20%, and the basalt and dolomite each accounted for 40%, and its chemical composition and calculated acidity coefficient are shown in Table 1; the mixed material 1 was loaded into a molybdenum crucible and placed in a BCT1700 high temperature viscosity melting point tester to test the relationship between the high temperature melt viscosity of the mixed material 1 and the temperature, and the results are shown in Table 2. Take a certain commercial mineral wool A and a certain commercial mineral wool B, and perform a chemical composition test and acidity coefficient calculation. The results are shown in Table 1. At the same time, the commercial mineral wool A and the commercial mineral wool B were tested for high temperature melt viscosity, and the results are shown in Table 2.
[0056] Table 2 Viscosity results of mixed material 1 and certain commercial mineral wool A and mineral wool B in the temperature range of 1250-1600℃ (Pa·s)
[0057] Temperature point / ℃ 1250 1300 1350 1400 1450 1500 1550 1600 Viscosity of mixed material 1 13.69 5.71 3.2 2.04 1.23 0.83 0.57 0.47 Viscosity of mineral wool A 32.85 15.67 9.14 4.93 2.95 1.78 1.25 0.81 Viscosity of mineral wool B 38.63 18.92 11.34 5.83 3.22 2.06 1.42 0.89
[0058] Example 2
[0059] The rest is consistent with Example 1, the only difference is that the lithium extraction tailings account for 30%, and the basalt and dolomite each account for 35%. That is, 30g of lithium extraction tailings, 35g of basalt and 35g of dolomite are taken to obtain a mixed material 2, and the chemical composition and high-temperature melt viscosity thereof are tested. The results are shown in Tables 3 and 4.
[0060] Table 3 Chemical composition analysis results of mineral wool production raw materials (percentage content)
[0061]
[0062] Table 4 Viscosity results of mixed material 2 and certain commercial mineral wool A and mineral wool B in the temperature range of 1250-1600℃ (Pa·s)
[0063] Temperature point / ℃ 1250 1300 1350 1400 1450 1500 1550 1600 Viscosity of mixed material 2 24.97 12.65 6.48 3.88 2.31 1.58 0.97 0.84 Viscosity of mineral wool A 32.85 15.67 9.14 4.93 2.95 1.78 1.25 0.81 Viscosity of mineral wool B 38.63 18.92 11.34 5.83 3.22 2.06 1.42 0.89
[0064] Example 3
[0065] The basic process is consistent with Example 1 and Example 2, the only difference is the ratio of basalt and dolomite. 10g of lithium extraction tailings, 67.5g of basalt, and 22.5g of dolomite are taken, that is, the lithium extraction tailings account for 10%, the basalt accounts for 67.5%, and the dolomite accounts for 22.5%. Mixture 3 is obtained and its chemical composition and high-temperature melt viscosity are tested. The results are shown in Tables 5 and 6.
[0066] Table 5 Chemical composition analysis results of mineral wool production raw materials (percentage content)
[0067]
[0068] Table 6 Viscosity results of mixed material 3 and certain commercial mineral wool A and mineral wool B in the temperature range of 1250-1600℃ (Pa·s)
[0069]
[0070] Example 4
[0071] According to the technical solution and Figure 1 In this embodiment, the residual tailings from lithium extraction from spodumene in Ya'an, Sichuan were used for relevant experiments. The chemical composition of the tailings and the chemical composition of basalt and dolomite in Sichuan are shown in Table 7. The acidity coefficient was calculated based on the chemical composition parameters.
[0072] Table 7 Chemical composition analysis results of mineral wool production raw materials (percentage content)
[0073]
[0074] Experimental process: 30g of lithium extraction tailings after drying pretreatment, 52.5g of basalt and 17.5g of dolomite were taken for mechanical mixing to obtain mixed material 4 (i.e., lithium extraction tailings accounted for 30%, basalt accounted for 52.5%, and dolomite accounted for 17.5%), and its chemical composition and calculated acidity coefficient are shown in Table 7; mixed material 4 was loaded into a molybdenum crucible and placed in a BCT1700 high temperature viscosity melting point tester to measure the relationship between the high temperature melt viscosity of mixed material 4 and the temperature change, and the results are shown in Table 8. Take a certain commodity mineral wool A and a certain commodity mineral wool B, and perform chemical composition tests and acidity coefficient calculations, the results are shown in Table 7, and at the same time, the high temperature melt viscosity of commodity mineral wool A and commodity mineral wool B was tested, and the results are shown in Table 8.
[0075] Table 8 Viscosity results of mixed material 4 and certain commercial mineral wool A and mineral wool B in the temperature range of 1250-1600℃ (Pa·s)
[0076] Temperature point / ℃ 1250 1300 1350 1400 1450 1500 1550 1600 Viscosity of mixed material 4 14.83 8.26 4.54 2.72 1.67 1.14 0.78 0.71 Viscosity of mineral wool A 32.85 15.67 9.14 4.93 2.95 1.78 1.25 0.81 Viscosity of mineral wool B 38.63 18.92 11.34 5.83 3.22 2.06 1.42 0.89
[0077] Example 5
[0078] The rest is consistent with Example 4, the only difference is that the lithium extraction tailings account for 20%, the basalt accounts for 60%, and the dolomite accounts for 20%. That is, 20g of lithium extraction tailings, 60g of basalt and 20g of dolomite are taken to obtain a mixed material 5, and the chemical composition and high-temperature melt viscosity thereof are tested. The results are shown in Tables 9 and 10.
[0079] Table 9 Chemical composition analysis results of mineral wool production raw materials (percentage content)
[0080]
[0081] Table 10 Viscosity results of mixed material 5 and certain commercial mineral wool A and mineral wool B in the temperature range of 1250-1600℃ (Pa·s)
[0082] Temperature point / ℃ 1250 1300 1350 1400 1450 1500 1550 1600 Viscosity of mixed material 5 17.58 10.23 5.46 3.12 1.93 1.35 0.86 0.75 Viscosity of mineral wool A 32.85 15.67 9.14 4.93 2.95 1.78 1.25 0.81 Viscosity of mineral wool B 38.63 18.92 11.34 5.83 3.22 2.06 1.42 0.89
[0083] Example 6
[0084] The rest is consistent with Example 4, the only difference is that the lithium extraction tailings account for 10%, basalt accounts for 70%, and dolomite accounts for 20%. That is, 10g of lithium extraction tailings, 70g of basalt and 20g of dolomite are taken to obtain a mixed material 6, and the chemical composition and high-temperature melt viscosity thereof are tested. The results are shown in Tables 11 and 12.
[0085] Table 11 Chemical composition analysis results of mineral wool production raw materials (percentage content)
[0086]
[0087] Table 12 Viscosity results of mixed material 6 and certain commercial mineral wool A and mineral wool B in the temperature range of 1250-1600℃ (Pa·s)
[0088] Temperature point / ℃ 1250 1300 1350 1400 1450 1500 1550 1600 Viscosity of mixed material 6 16.34 9.85 5.17 3.06 1.82 1.29 0.83 0.74 Viscosity of mineral wool A 32.85 15.67 9.14 4.93 2.95 1.78 1.25 0.81 Viscosity of mineral wool B 38.63 18.92 11.34 5.83 3.22 2.06 1.42 0.89
[0089] The results of Examples 1 to 6 of the present invention show that doping with residual tailings from lithium extraction from spodumene can regulate the high-temperature melt viscosity of the raw materials for mineral wool production. Using the method of the present invention, the tailings from lithium extraction can account for 10 to 30% of the raw materials for mineral wool production. The acidity coefficient of the mixed material (composed of basalt, dolomite and tailings from lithium extraction) used for mineral wool production is between 1.37 and 1.77, and the high-temperature melt viscosity is 0.57 to 6.48 Pa·s in the temperature range of 1350 to 1550°C, which meets the use standard for mineral wool production. At the same time, the results of Examples 1 to 6 show that doping with residual tailings from lithium extraction can improve the high-temperature melt fluidity of the mixed material for mineral wool production, which is beneficial to the melting of the mixed material, and the appropriate melt viscosity for mineral wool production can be obtained at a relatively low temperature, thereby facilitating energy saving and consumption reduction in the mineral wool production process.
[0090] The results of Examples 1 to 6 of the present invention also show (see Figure 2 and Figure 3), compared with the traditional acidity coefficient calculation formula, i.e., the ratio of the sum of SiO2+Al2O3 contents to the sum of CaO+MgO contents, the preferred acidity coefficient formula of the present invention, i.e., the ratio of the sum of SiO2+Al2O3+TiO2 contents to the sum of Fe2O3+CaO+MgO+Na2O+K2O contents, can better reflect the melt viscosity of the mineral wool production mixture under the high temperature conditions of normal mineral wool production, wherein the acidity coefficient of the mineral wool production raw material obtained by the acidity coefficient calculation formula of the present invention has a strong positive correlation with its high temperature melt viscosity (see Figure 2 , R 2 >0.86), while the traditional acidity coefficient calculation formula cannot effectively predict the high temperature melt viscosity of mineral wool production raw materials (see Figure 3 , R 2 <0.40). It can be seen that the preferred acidity coefficient calculation formula of the present invention can more effectively and accurately guide the industrial production practice of mineral wool.
Claims
1. A method for regulating the melt viscosity of mineral wool using spodumene lithium extraction tailings, characterized in that: The method comprises: The lithium extraction tailings are mixed with basalt and dolomite to obtain a mixed material, and the mixed material is subjected to a heat treatment to obtain a high-temperature melt; the acidity coefficient of the mixed material is calculated using formula (I): Acidity coefficient = [M(SiO2)+M(Al2O3)+M(TiO2)] / [M(Fe2O3)+M(CaO)+M(MgO)+M(Na2O)+M(K2O)] formula (I); Among them, M(SiO2), M(Al2O3), M(TiO2), M(Fe2O3), M(CaO), M(MgO), M(Na2O), and M(K2O) represent the mass percentage of silicon dioxide, aluminum oxide, titanium dioxide, iron oxide, calcium oxide, magnesium oxide, sodium oxide, and potassium oxide, respectively, in the form of oxides.
2. The method for regulating the melt viscosity of mineral wool by using spodumene to extract lithium tailings according to claim 1, characterized in that: The lithium extraction tailings are pre-treated by drying to make its moisture content lower than 3wt%.
3. The method for regulating the melt viscosity of mineral wool using spodumene-based lithium tailings according to claim 1 or 2, wherein: The particle sizes of the lithium extraction tailings, basalt and dolomite are less than 0.074 mm.
4. The method for regulating the melt viscosity of mineral wool using spodumene-based lithium tailings according to claim 1 or 2, wherein: The content of lithium-extracting tailings in the mixed material is 10wt% to 30wt%, the content of dolomite is 17.5wt% to 40wt%, and the rest is basalt.
5. The method for regulating the melt viscosity of mineral wool using spodumene-based lithium tailings according to claim 1 or 2, wherein: The lithium extraction tailings has a SiO2 content of 54.06wt% to 70.6wt%, an Al2O3 content of 22.03wt% to 25.39wt%, a TiO2 content of 0.03wt% to 0.08wt%, a CaO content of 0.99wt% to 7.7wt%, a MgO content of 0.04wt% to 0.09wt%, a Fe2O3 content of 0.9wt% to 1.34wt%, a Na2O content of 0.05wt% to 0.36wt%, and a K2O content of 0.55wt% to 0.85wt%.
6. The method for regulating the melt viscosity of mineral wool using spodumene-based lithium tailings according to claim 1 or 2, wherein: The dolomite has a SiO2 content of 9.24wt% to 16.26wt%, an Al2O3 content of 1.83wt% to 2.64wt%, a TiO2 content of 0.2wt% to 1.84wt%, a CaO content of 32.68wt% to 53.97wt%, a MgO content of 18.52wt% to 24.37wt%, a Fe2O3 content of 1.85wt% to 2.02wt%, a Na2O content of 0.06wt% to 1.32wt%, and a K2O content of 0.38wt% to 1.06wt%.
7. The method for regulating the melt viscosity of mineral wool using spodumene-based lithium tailings according to claim 1 or 2, wherein: The basalt has a SiO2 content of 43.99wt% to 52.84wt%, an Al2O3 content of 13.52wt% to 14.03wt%, a TiO2 content of 2.81wt% to 3.32wt%, a CaO content of 7.35wt% to 10.4wt%, a MgO content of 4.94wt% to 8.73wt%, a Fe2O3 content of 8.26wt% to 16.01wt%, a Na2O content of 1.67wt% to 2.23wt%, and a K2O content of 2.15wt% to 3.27wt%.
8. The method for regulating the melt viscosity of mineral wool using spodumene-extracted lithium tailings according to claim 1 or 2, characterized in that: The acidity coefficient is 1.37 to 1.
77.
9. Regulating mineral wool by using tailings from lithium extraction from spodumene, characterized in that: The mineral wool is prepared by the method for regulating the melt viscosity of mineral wool using spodumene lithium extraction tailings as described in any one of claims 1 to 8.
10. The method of claim 9 wherein the spodumene-based lithium tailings are used to control mineral wool, The high-temperature melt viscosity of the mineral wool is 0.57-6.48 Pa·s in the temperature range of 1350-1550°C.
Citation Information
Patent Citations
Full-phase high-valued recycling method for lithium slag
CN108273826A
Porous self-loading zeolite material prepared from acid-process lithium slag as well as preparation method and application of porous self-loading zeolite material
CN111018422A
Method for producing early strength cement from lithium slag
CN114249549A
Method for adsorbing and extracting lithium from brine by adopting lithium smelting slag
CN115323195A
Comprehensive recycling method for extracting silicon and aluminum from lithium slag
CN115448318A